Game backend development : with Microsoft Azure and Playfab - Bors, Balint (Apress, 2023)
Up your game developer skills by learning game backend development with Microsoft Azure and PlayFab. Robust backend infrastructure support is essential for all modern games. Implementing game backend features became easier with the emergence of GBaaS (Game Backend-as-a-Service) providers and the advance of the cloud. Multiplayer gaming, leaderboards, game analytics, and virtual economies are all backed by cloud services. As a game developer, understanding core game backend features and implementation techniques is an important addition to your game developer skill set. Understanding game backend development will not only give you a competitive advantage, it will also eventually allow you to create better games. This book will help you get started. It teaches all the core concepts, using downloadable source code, so that you can experiment right away following a learning-by-doing approach. After reading this book, you will have a solid grasp of key game backend services and know how to implement them. What You Will Learn Understand core concepts around game backend development Use the PlayFab API to implement backend features Build game backend infrastructure using Microsoft Azure cloud (architecture and implementation) Contrast the traditional Azure cloud- and PlayFab (GBaaS)-based implementations of game backend capabilities Reuse source code to enable backend capability in your own games Discover different ways for authenticating players Implement a multiplayer game in Unity with the help of mirror networking Create a matchmaker to bring together players for an online game session Establish leaderboards to reinforce player competition Build a virtual economy and monetize your game Set up game analytics and gain insight into players' behavior Let players communicate with each other by taking advantage of cognitive services Learn how to implement server-side custom game backend logic Who This Book Is For Game developers who may be skilled in game development, but who possess little to no skills in GBaaS and cloud computing. This book is also for professionals working in the cloud solutions space who want to learn about the specific challenges of the gaming domain.